Achieving Social Peace from the Perspective of Islamic Studies (Islamic Sciences Journal, 2025)
ABSTRACTThis research addresses the importance of social peace as one of the fundamental pillars for the stability and cohesion of societies, from an Islamic perspective based on the Glorious Qur’an and the Prophetic Sunnah. It is based on the hypothesis that Islam, with its system of values and ethics, has laid the foundation for a culture of peace, tolerance, and dialogue, making these values central to the construction of social and human relationships.Research Methodology: The study is divided into an introduction, five sections, and a conclusion:• Section One: General concepts of social peace.• Section Two: Social peace in the Qur’an and Sunnah• Section Three: Foundations of social peace in Islam.• Section Four: The role of societal institutions in promoting peace.• Section Five: Challenges facing social peace, which is divided into three subsections.